The New Disciple - Ban, Arline J.; Joseph D. Ban (Valley Forge, Pa. Judson Press, 1976)
A discussion of what it means to be a disciple of Christ in today's world aimed at young people who are thinking about joining an American Baptist church.
Keywords: Baptists -- Membership -- Juvenile literature. Christian life -- Baptist authors -- Juvenile literature. Baptists -- Doctrines -- Juvenile literature